2007
DOI: 10.1038/sj.leu.2404621
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells are abnormal in multiple myeloma

Abstract: Recent literature suggested that cells of the microenvironment of tumors could be abnormal as well. To address this hypothesis in multiple myeloma (MM), we studied bone marrow mesenchymal stem cells (BMMSCs), the only long-lived cells of the bone marrow microenvironment, by gene expression profiling and phenotypic and functional studies in three groups of individuals: patients with MM, patients with monoclonal gamopathy of undefined significance (MGUS) and healthy agematched subjects. Gene expression profile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
320
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(361 citation statements)
references
References 62 publications
28
320
1
4
Order By: Relevance
“…In spite of the hosts' response to the implanted cells, human Dkk-1 could be detected in the blood of the recipient mice, demonstrating that tumour-derived Dkk-1 escapes into the blood It is unclear at this point whether the elevated systemic Dkk-1 in OS patients is derived solely from the tumour, since the human Dkk-1 circulating in the blood of recipient mice was much lower than the mean levels detected in the blood of the human OS patients. It is possible, however, that the host tissue interacts with the tumour, resulting in upregulation of the expression of Dkk-1, a phenomenon observed in the case of multiple myeloma (Gunn et al, 2005;Corre et al, 2007). The host microenvironment in the patients may be more readily affected by the tumour than the surrounding mouse tissue accounting for the reduced levels of Dkk-1 in the mouse blood when compared to the human blood.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the hosts' response to the implanted cells, human Dkk-1 could be detected in the blood of the recipient mice, demonstrating that tumour-derived Dkk-1 escapes into the blood It is unclear at this point whether the elevated systemic Dkk-1 in OS patients is derived solely from the tumour, since the human Dkk-1 circulating in the blood of recipient mice was much lower than the mean levels detected in the blood of the human OS patients. It is possible, however, that the host tissue interacts with the tumour, resulting in upregulation of the expression of Dkk-1, a phenomenon observed in the case of multiple myeloma (Gunn et al, 2005;Corre et al, 2007). The host microenvironment in the patients may be more readily affected by the tumour than the surrounding mouse tissue accounting for the reduced levels of Dkk-1 in the mouse blood when compared to the human blood.…”
Section: Resultsmentioning
confidence: 99%
“…HMCLs U266, RPMI-8226, LP-1, OPM-2 and SKMM-2 were purchased from DSMZ (Braunschweig, Germany), and XG lines were generated at INSERM U847 (Montpellier, France) as published previously (Zhang et al, 1994). PPCs (Tarte et al, 2002), osteoclasts ) and MSCs (Corre et al, 2007) were generated as published.…”
Section: Samplesmentioning
confidence: 99%
“…Several previous studies indicated that BM-derived MSCs from MM patients showed an enhanced production of cytokines and a distinctive gene expression profile, as compared with their normal counterparts. [1][2][3][4] Although osteoblastic function is decreased in advanced MM, regarding whether and at which level the differentiation of MSCs towards osteoblasts is impaired in this disease, the reports are not unanimous. [1][2][3] In the present study, MSCs from both normal subjects (healthy human donors or naive mice) and MM subjects (MM patients or 5T33MM mice) were used.…”
mentioning
confidence: 99%
“…[1][2][3][4] Although osteoblastic function is decreased in advanced MM, regarding whether and at which level the differentiation of MSCs towards osteoblasts is impaired in this disease, the reports are not unanimous. [1][2][3] In the present study, MSCs from both normal subjects (healthy human donors or naive mice) and MM subjects (MM patients or 5T33MM mice) were used. The 5T33MM mice originate from elderly C57Bl/KaLwRij mice that spontaneously developed MM, and the MM model is propagated by intraveneous transfer of diseased BM cells into young syngeneic mice.…”
mentioning
confidence: 99%